Bond market development in Asia: An empirical analysis of major determinants - Biswa Nath Bhattacharyay (Asian Development Bank Institute (ADBI), 2011)
One of the reasons behind the financial crisis in 1997 was excessive dependence of Asian economies on commercial banks for domestic financing. Banks were the major source of corporate financing because the other major source, bond markets, was underdeveloped and small. On the other hand, the 2008 global financial crisis led to constraints in acquiring local currency and foreign currency liquidity in the corporate sector, as foreign banks withdrew investments from Asia. Furthermore, Asia needs large quantities of capital (US750 billion per year for 2010-2020) to develop infrastructure connectivity within and across its economies. Local and regional capital can be channeled for long-term infrastructure projects and other productive investment through bond markets. At this juncture, to enhance bond financing, it is important to examine factors that promote effective development of bond markets. This study attempts to identity the major determinants of bond market development in Asian economies, through examining its relationship with selected key financial and economic factors, and to provide policy recommendations for further developing Asian bond markets. Major determinants for bond market development in Asia include the size of an economy, the stage of economic development, the openness of an economy, the size of the banking sector, and the interest rate spread.
Keywords: F36; O16; G15; O53; 330; Rentenmarkt; Kapitalmarktliberalisierung; Asien